PENGARUH LIKUIDITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Khusnul Khasanah; Nyimas Wardatul Afiqoh (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2022)
This research aims to analyze the effect of liquidity, leverage, and firm size on tax avoidance with independent commissioners as moderating variables. The research population is basic and chemical industrial companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique used purposive sampling technique which resulted in a sample of 70 data. The source of the research data is secondary data, namely the company's annual financial report data from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. Data analysis used moderated regression with the absolute difference value method. The results of this study indicate that liquidity and firm size affect tax avoidance, while leverage has no effect on tax avoidance. Furthermore, the moderating results show that the independent commissioners cannot moderate (weaken) the effect of liquidity, leverage, and firm size on tax avoidance.